ENHANCING CAPACITY OF LOCAL COMMUNITY TOWARDS AGRICULTURAL DROUGHT (CASE IN PLOSO VILLAGE, YOGYAKARTA) - Dina Ruslanjari (Universitas Gadjah Mada, 2017)
This paper reveals the capacity enhancement efforts for local community and assessing their vulnerability level regarding the drought event in Ploso Village of Gunungkidul Regency – Yogyakarta Special Province. The vulnerability assessment was conducted to measure the impact of agricultural drought and also focusing on enhancing the community’s absorbing capacity, buffering capacity and local response capacity. The village drought vulnerability assessment was conducted by using indicator-based calculation towards 50 family-heads of Ploso Village as the assessment samples. Absorbing capacity enhancement was conducted by facilitating and educating local farmers to conduct organic farming as well as increasing their local response capacity by focusing on rainwater harvesting, while buffering capacity enhancement is conducted by empowering the housewives for creating alternate household income The disaster preparedness community is created as the centre of intervention to educate local people about drought disaster and preparing the local teenagers to become future focal points in their area.